Why is trait scepticism not consistently reflected in state scepticism? An exploratory study into the role of aesthetic engagement. (9th August 2019) - Khan, Mohammad Jahanzeb; Harding, Noel
Abstract: Where an auditor's sceptical disposition (trait scepticism) is directed toward non‐diagnostic information, there is a risk that a sceptical consideration of diagnostic information could be diluted. This may be one reason why trait scepticism is not consistently reflected in sceptical judgments and actions (state scepticism). We develop a scale to measure an individual's predisposition toward engaging with visual elements of the environment (aesthetic engagement) and test, in two experiments employing students and practicing auditors, whether aesthetic engagement moderates the trait – state scepticism relationship. We find that aesthetic engagement attenuates the positive relationship between trait and state scepticism.